The Relationship Level of Critical Thinking Ability and Student Learning Outcomes in Invertebrata Materials - Lia Tania Barka; Purwati Kuswarini Suprapto; Vita Meylani (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2020)
The ability to think critically has a pattern of thinking that can improve learning outcomes, because it can provide new ideas to solve a problem. This study aims to determine the relationship between critical thinking skills and student learning outcomes in invertebrate material. This research was conducted from March to May 2020 in one of the high schools in Tasikmalaya. The research method used is the correlational method with a population of all class X math and science students as many as 6 classes. Samples were taken by using purposive sampling as many as 2 classes namely class X math and science 3 and X math and science 4. Data collection techniques carried out by giving posttest as many as 8 items in the form of description to measure critical thinking skills and 25 items in the form of multiple choice to measure student learning outcomes . The data analysis technique used is correlation regression with α 0.05. The results of the research, data analysis and hypothesis testing show that there is a positive correlation between the ability to think critically with student learning outcomes on invertebrate material. with a yield of 24.2% and fall into the medium category.